Population changes in Gharial (Gavialis gangeticus) vary spatially in Chitwan National Park, Nepal - Khadka, Bed Bahadur; Bashyal, Ashish; Griffith, Phoebe (Reptiles & Amphibians, 2024)
Gharials, large crocodilians found only in South Asia, are widely seen as a flagship species for river conservation in Nepal, especially in Chitwan National Park, where a headstart program has supplemented the population since 1981. The population has shown signs of recovery only in the last decade, so continued monitoring of population trends is vital for conservation. We conducted annual winter population surveys for gharial in Chitwan between 2017 and 2022, during which we also characterized riverbank substrate availability and basking preferences. We documented potential threats to the species in Chitwan throughout the year. Overall, we counted an increasing number of Gharials in Chitwan; however mixed-effects modelling of Gharial encounter rate showed that increasing encounters rates are not evenly distributed throughout available habitat, with some river stretches having stable or decreasing trends. Encounter rates on the Rapti River increased in all transects, compared to more variable results on the Narayani River, likely attributable to higher levels of human disturbance and the impact of captivity on habitat selection. Fewer Gharials were seen in transects with high levels of disturbance due to sand mining and the extraction of river substrates, highlighting this threat as a major concern. Regular reports of bycatch in illegal gillnets was the major observed source of mortality. A lack of an increasing population trend in the stretch above a large barrage suggests that recruitment is minimal in this area, and the dam likely has a negative impact on upstream Gharial recruitment. We cautiously suggest that the Chitwan population is recovering, but that recovery is hampered by threats, especially substrate extraction, illegal gillnet fishing, and river fragmentation by a dam.